2012
DOI: 10.1111/j.1365-313x.2012.05120.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of marneral synthase, which is critical for growth and development in Arabidopsis

Abstract: SUMMARYPlants produce structurally diverse triterpenoids, which are important for their life and survival. Most triterpenoids and sterols share a common biosynthetic intermediate, 2,3-oxidosqualene (OS), which is cyclized by 2,3-oxidosqualene cyclase (OSC). To investigate the role of an OSC, marneral synthase 1 (MRN1), in planta, we characterized a Arabidopsis mrn1 knock-out mutant displaying round-shaped leaves, late flowering, and delayed embryogenesis. Reduced growth of mrn1 was caused by inhibition of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 71 publications
(138 reference statements)
1
34
0
1
Order By: Relevance
“…a,b). These pathways have both been implicated in development and in ecological interactions (Field & Osbourn, 2008; Field et al ., 2011; Go et al ., 2012). The genes within each of these two clusters are co-regulated and are expressed exclusively in roots (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…a,b). These pathways have both been implicated in development and in ecological interactions (Field & Osbourn, 2008; Field et al ., 2011; Go et al ., 2012). The genes within each of these two clusters are co-regulated and are expressed exclusively in roots (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“… [74] , [75] . MRN1 is involved in the biosynthetic pathway of triterpenoids and plays a critical role in growth and development in Arabidopsis [76] . Loss-of-function in Arabidopsis MRN1 caused various phenotypic changes in plant growth and development and also significantly increased electrolyte leakage compared with that of wild-type [76] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these effects could not be attributed to the altered expression of genes involved in cell expansion, while it is unknown whether marneral and its derivatives serve as membrane constituents. At the transcriptional level, these compounds have been proposed to have a negative role in flower development, since the delayed flowering phenotype in the mrn1 knockout mutant could be attributed to increased expression of the flowering locus C ( FLC ) gene that encodes a repressor of flowering in A. thaliana (Go et al ., 2012 ).…”
Section: Effects On Plant Growth and Developmentmentioning
confidence: 99%
“…However, very little is known about the temporal and spatial embedding of these molecules in the membranes or the role that they may play during normal plant growth. Triterpenes may substitute sterols at certain developmental stages as has been suggested for marneral (Go et al ., 2012 ), or they may have functions in various physiological processes such as nodule formation and cuticle composition. It has also been suggested that isoprenoids, unidentified as yet but other than sterols, are responsible for the activity of plant microRNAs (miRNAs) that guide ARGONAUTE (AGO) protein complexes to regulate expression of complementary RNAs.…”
Section: Effects On Plant Growth and Developmentmentioning
confidence: 99%